Child Developmental Screening Test & Progress Monitoring System For Little Ones Eduworld Therapy Centre - Aina Safia, Jeffree (2023)
The age of five years old is known as a golden age for the children to have the opportunity to learn and experience things in their life through their surroundings. However, there are still many children that are facing and suffering with delay in their growth development. In that case, these children need special care and support to monitor their development. A method of screening test is performed to identify the potential delay in a child’s development. As the screening test method is mostly done in manual way, there are some disadvantages that are faced. As the LOE Therapy Center and MZR company known as the clients, they mentioned that many screening test tasks needed to be taken care of for four main development areas and the number of children that facing the developmental delay is also large that needed to be recorded and saved for future used. Besides, the screening result is also based on the Denver Scale that needed to be cross-check with the children’ age. In that case, the manual system is not efficient and suitable to handle and store a lot of data and information and very time consuming. Scrum methodology is used throughout the system development as an iterative and incremental approach that have continuous Sprints with clients for progress update regularly through meeting and discuss on adjustments, improvements and feedback for the project. Therefore, a digital system known as CDST system, a web-based system will be designed and developed for the purpose of performing the screening test to detect any developmental delay and monitor the child’s development progress. The system will be used to monitor child’s development progress in short time. In addition, the system also can manage and handle a lot of data needed more effectively and efficiently and will be securely stored in the system database for the future used. Lastly, the finalize CDST system is tested by client which is MZR and gained positive feedback from clients of MZR of the functionality, usability and effectiveness of the system and also some minor improvement that can be implemented.